2006
DOI: 10.1140/epje/e2006-00018-3
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte multilayer formation: Electrostatics and short-range interactions

Abstract: We investigate the phenomenon of multilayer formation via layer-by-layer deposition of alternating charged polyelectrolytes. Using mean-field theory, we find that a strong short-range attraction between the two types of polymer chains is essential for the formation of multilayers. For strong enough short-range attraction, the adsorbed amount per layer increases (after an initial decrease), and finally it stabilizes in the form of a polyelectrolyte multilayer that can be repeated hundreds of times. For weak sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 51 publications
2
47
0
Order By: Relevance
“…Following these authors, their model does not apply to the low ionic strength situation where the range of the Coulombic forces is too large. Shafir and Andelman described the importance to reach sufficiently strong short range interactions between the oppositely charged polymers to obtain a regular growth of the LBL film 69…”
Section: Physicochemical Aspects Allowing To Control the Lbl Deposmentioning
confidence: 99%
“…Following these authors, their model does not apply to the low ionic strength situation where the range of the Coulombic forces is too large. Shafir and Andelman described the importance to reach sufficiently strong short range interactions between the oppositely charged polymers to obtain a regular growth of the LBL film 69…”
Section: Physicochemical Aspects Allowing To Control the Lbl Deposmentioning
confidence: 99%
“…The numerical solutions of the self-consistent field equations describing multilayer assembly have been recently presented by Wang [138,139] and by Shafir and Andelman [140] These calculations have shown that the sufficiently strong short-range attraction between oppositely charged polymers is essential for the formation of multilayers. The limitation of the used approach is that after completion of each deposition step the polymer density distribution of polyelectrolytes adsorbed during this deposition step was fixed for the remaining duration of the film growth process.…”
Section: Layer-by-layer Assemblymentioning
confidence: 99%
“…There is a large body of theoretical and computational work [16][17][18][19][20][21][22][23][24][25][26] on the adsorption of charged polymers to surfaces ͑the literature is reviewed elsewhere 9 ͒. There have been very few simulations that have focused on the effect of solvent quality on adsorption.…”
Section: Introductionmentioning
confidence: 99%